Managing Quantity, Quality, and Timing in Indian Cane Sugar Production : Ex Post Marketing Permits or Ex Ante Production Contracts? - Patlolla, Sandhyarani (World Bank Group, Washington, DC, 2014)
Private sugar processors in Andhra Pradesh, India use an unusual form of vertical coordination. They issue 'permits' to selected cane growers a few weeks before harvest. These permits specify the amount of cane to be delivered during a narrow time period. This article investigates why processors create uncertainty among farmers using ex post permits instead of ex ante production contracts. The theoretical model predicts that ex post permits are more profitable than ex ante contracts or the spot market under existing government regulations in the sugar sector, which include a binding price floor for cane and the designation of a reserve area for each processor wherein it has a legal monopsony for cane. The use of ex post permits creates competition among farmers to increase cane quality, which increases processor profits and farmer costs. Empirical analysis supports the hypothesis that farmers operating in private factory areas have higher unit production costs than do their counterparts who patronize cooperatives.